Francisella philomiragia Infection and Lethality in Mammalian Tissue Culture Cell Models, Galleria mellonella, and BALB/c Mice - Propst, Crystal N.; Pylypko, Stephanie L.; Blower, Ryan J.; Ahmad, Saira; Mansoor, Mohammad; van Hoek, Monique L. (Frontiers in Microbiology, 2016)
Francisella (F.) philomiragia is a Gram-negative bacterium with a preference for brackish environments that has been implicated in causing bacterial infections in near-drowning victims. The purpose of this study was to characterize the ability of F. philomiragia to infect cultured mammalian cells, a commonly used invertebrate model, and, finally, to characterize the ability of F. philomiragia to infect BALB/c mice via the pulmonary (intranasal) route of infection. This study shows that F. philomiragia infects J774A.1 murine macrophage cells, HepG2 cells and A549 human Type II alveolar epithelial cells. However, replication rates vary depending on strain at 24 hours. F. philomiragia infection after 24 hours was found to be cytotoxic in human U937 macrophage-like cells and J774A.1 cells. This is in contrast to the findings that F. philomiragia was noncytotoxic to human hepatocellular carcinoma cells, HepG2 and A549 cells. Differential cytotoxicity is a point for further study. Here it was demonstrated that F. philomiragia grown in host-adapted conditions (BHI, pH 6.8) is sensitive to levofloxacin but shows increased resistance to the human cathelicidin LL-37 and murine cathelicidin mCRAMP when compared to related the Francisella species, F. tularensis subsp. novicida and F. tularensis subsp. LVS. Previous findings that LL-37 is strongly upregulated in A549 cells following F. tularensis subsp. novicida infection suggest that the level of antimicrobial peptide expression is not sufficient in cells to eradicate the intracellular bacteria. Finally, this study demonstrates that F. philomiragia is lethal in two in vivo models; Galleria mellonella via injection, with a LD50 of 1.8x10^3, and BALB/c mice by intranasal infection, with a LD50 of 3.45x10^3. In conclusion, F. philomiragia may be a useful model organism to study the genus Francisella, particularly for those researchers with interest in studying microbial ecology or environmental strains of Francisella. Additionally, the Biosafety-level two status of F. philomiragia makes it an attractive model for virulence and pathogenesis studies.